MODEL PENINGKATAN KINERJA PEMASARAN MELALUI FAKTOR KARAKTERISTIK PIMPINAN, ORIENTASI PASAR DAN ORIENTASI PEMBELAJARAN (Studi Pada UMKM Patung dan Ukir Di Sentra Industri Mulyoharjo Jepara) - Sarwido Sarwido (Jurnal Riset Bisnis Indonesia, 2013)
Leaders as the top management plays crucial role in assuring the success of every organizationprograms aimed at achieving the excellence of marketing performance. To get prominent marketingperformance it required an organization culture which allowing implementing marketing concept toachieve the excellence of marketing performance as a market orientation. Nevertheless, it appearsan assumption that only market orientation is not sufficient so requiring firms to learn faster thantheir competitors. It needs also organization characteristics that are able to develop learning abilitywithin organization that is learning-oriented led to improve understanding toward markets and as awhole would imply customer’s response in line with firms’ expectation. In this context, it is proposed aresearch model to analyze the relation between leaders’ characteristics and market orientation, marketorientation and marketing performance, and learning orientation and marketing performance. Thisstudy used 62 sample managers or company leader of statue and relief in industry centric MulyoharjoJepara through purposive sampling technique. Data collection was undertaken by way of personallyadministered questionnaires which the analyzed with Smart Partial Least Square (PLS). From theresearch, it is concluded that learning orientation has a positive effect on organization marketingperformance, market orientation has a positive effect on organization marketing performance, andleaders’ characteristic has a positive effect on market orientation.Keywords: Leaders Characteristic, Market Orientation, Learning Orientation, MarketingPerformance